Synthèse et conclusions sur la gestion durable des zones côtières et marines. Au-delà des discours, des enjeux opérationnels pour le développement durable ? - Agnès Michelot (VertigO)
The symposium on “Sustainable management of coastal and marine areas : new views, new sustainabilities, new frontiers” which took place in La Rochelle (France) on 10th and 11th of june 2010 leads to address concrete issues on sustainable development in coastal and marine areas. Presentations from lawyers, political scientists, biologists and geographers contribute to present a cross approach on the concept of Integrated Coastal Zone Management (ICZM) oriented to the maritime dimension. Depending to views, legal texts and the evolution of scientific knowledge, the concept is submitted to adaptations opening new perspectives to achieve sustainable management related to an integrated and responsible approach fixed in a participative process. The La Rochelle Symposium invites to discover new “frontiers” of ICZM, which means study of its recent potentialities and experimentations linked to adequate decision making process, taking into account an especially evolutive context at global, national and local levels.